Study of calcification formation and disease diagnostics utilising advanced vibrational spectroscopy - Kerssens, Marleen Maartje (Cranfield University, 2012)
The accurate and safe diagnosis of breast cancer is a significant societal issue, with annual disease incidence of 48,000 women and around 370 men in the UK. Early diagnosis of the disease allows more conservative treatments and better patient outcomes. Microcalcifications in breast tissue are an important indicator for breast cancers, and often the only sign of their presence. Several studies have suggested that the type of calcification formed may act as a marker for malignancy and its presence may be of biological significance. In this work, breast calcifications are studied with FTIR, synchrotron FTIR, ATR FTIR, and Raman mapping to explore their disease specific composition. From a comparison between vibrational spectroscopy and routine staining procedures it becomes clear that calcium builds up prior to calcification formation. Raman and FTIR indicate the same size for calcifications and are in agreement with routine staining techniques. From the synchrotron FTIR measurements it can be proven that amide is present in the centre of the calcifications and the intensity of the bands depends on the pathology. Special attention is paid to the type of carbonate substitution in the calcifications relating to different pathology grades. In contrast to mammography, Raman spectroscopy has the capability to distinguish calcifications based on their chemical composition. The ultimate goal is to turn the acquired knowledge from the mapping studies into a clinical tool based on deep Raman spectroscopy. Deep Raman techniques have a considerable potential to reduce large numbers of normal biopsies, reduce the time delay between screening and diagnosis and therefore diminish patient anxiety. In order to achieve this, a deep Raman system is designed and after evaluation of its performance tested on buried calcification standards in porcine soft tissue and human mammary tissue. It is shown that, when the calcification is probed through tissue, the strong 960 cm-1 phosphate band can be used as a pseudo marker for carbonate substitution which is related to the pathology of the surrounding tissue. Furthermore, the first study in which human breast calcifications are measured in bulk tissue with a thickness of several millimetres to centimetres is presented. To date, measurements have been performed at 41 specimens with a thickness up to 25 mm. Measurements could be performed through skin and blue dye. The proposed deep Raman technique is promising for probing of calcifications through tissue but will need refinement before being adopted in hospitals.
Keywords: Breast cancer; apatite; FTIR (Fourier Transform InfraRed); synchrotron FTIR; ATR (attenuated total reflection); Raman mapping; deep Raman; Transmission Raman spectroscopy